1998
DOI: 10.1111/j.1746-1561.1998.tb03491.x
|View full text |Cite
|
Sign up to set email alerts
|

Principles for Developing Interdisciplinary School‐based Primary Care Centers

Abstract: A 50% increase has occurred in the number of school-based primary care centers (SBPCCs) in the United States since 1993-94. Public schools offer a well-established and respected community-based infrastructure within which health centers may feasibly be developed. SBPCCs have documented improved access to care for underserved children and some initial success in addressing the complex morbidities and associated behavioral risk factors of children and adolescents. This paper presents five working principles to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Existing school health advisory councils within the majority of schools or districts can assist in these activities and reduce the burden. 3,13,73,75 Additionally, the SBHA has been a resource to pediatricians and an advocate for the implementation and ongoing operation of SBHCs. 76 To support the medical home model, communication among the stakeholders (school, SBHCs, and community primary care providers) needs to occur from the planning stages to the operational stages.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing school health advisory councils within the majority of schools or districts can assist in these activities and reduce the burden. 3,13,73,75 Additionally, the SBHA has been a resource to pediatricians and an advocate for the implementation and ongoing operation of SBHCs. 76 To support the medical home model, communication among the stakeholders (school, SBHCs, and community primary care providers) needs to occur from the planning stages to the operational stages.…”
Section: Challengesmentioning
confidence: 99%
“…Guidelines include community needs assessment, coordination of care with the medical community, and measurement of performance indicators reflecting the effect of SBHC services on students' health and academic outcomes. [12][13][14][15] According to the SBHA, the 7 core competencies of SBHCs are 16 as follows:…”
mentioning
confidence: 99%
“…Encourage the development of school health advisory councils to establish a setting for planning, monitoring, and developing SBHCs and coordinated school health services. 12,59,60 …”
Section: Challengesmentioning
confidence: 99%
“…As the medical home concept has evolved, SBHCs fit into the model just as satellite offices and practice networks do for private practice. 12 A recent national survey of SBHCs revealed that 35% of managed care organizations recognize SBHCs as reimbursable primary care providers. 1 …”
mentioning
confidence: 99%
See 1 more Smart Citation